Les élections roumaines : le poids du passé - Octavian Groza; Catrinel Trofin-Gille (Belgeo)
Since 1989 Romania has been experiencing the avatars of the rediscovery of the local and regional dimensions of the territorial building. The phenomenon is very complicated because Romania is a complex territory characterized by deep tensions determined by the quick and recent construction of the modern Romanian State. This paper explores, through a geographical analysis of the elections, the decrease of the ethnical tensions and demonstrates the slow emergence of a civic behaviour on the part of Romanian citizens. The process is characterized by a slow affirmation of local and regional structures as a reaction to centralizing trends inherited from communism.